2022
DOI: 10.1186/s12974-022-02460-8
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus-induced TNF-α signaling dysregulates expression of neurologic genes associated with psychiatric disorders

Abstract: Background Zika virus (ZIKV) is an emerging flavivirus of global concern. ZIKV infection of the central nervous system has been linked to a variety of clinical syndromes, including microcephaly in fetuses and rare but serious neurologic disease in adults. However, the potential for ZIKV to influence brain physiology and host behavior following apparently mild or subclinical infection is less well understood. Furthermore, though deficits in cognitive function are well-documented after recovery f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 124 publications
(62 reference statements)
0
11
0
Order By: Relevance
“…Although the expressions of these inflammatory genes can elicit an antiviral response, several of these molecules represent senescence markers, and chronic neuroinflammation is a common feature of neuropsychiatric and neurodegenerative diseases, such as AD, ASD, ALS, PD, epilepsy, multiple sclerosis, and schizophrenia. Accordingly, in vitro mechanistic studies have identified TNF‐α signaling via TNFR1 as a crucial regulatory mechanism controlling ZIKV‐induced changes in neurologic gene expression (Kung et al, 2022). Several genes associated with cell functionality have been identified, particularly in astrocytes, including GFAP , BDNF , SOD2 , SLC1A3 , MAOA , ACHE , APOE , LDLR , which encode astrocyte markers and proteins associated with trophic signaling, antioxidant defenses, neurotransmitter homeostasis and cholesterol metabolism.…”
Section: Zikv Infection and Potential Neurological Complications Rela...mentioning
confidence: 99%
“…Although the expressions of these inflammatory genes can elicit an antiviral response, several of these molecules represent senescence markers, and chronic neuroinflammation is a common feature of neuropsychiatric and neurodegenerative diseases, such as AD, ASD, ALS, PD, epilepsy, multiple sclerosis, and schizophrenia. Accordingly, in vitro mechanistic studies have identified TNF‐α signaling via TNFR1 as a crucial regulatory mechanism controlling ZIKV‐induced changes in neurologic gene expression (Kung et al, 2022). Several genes associated with cell functionality have been identified, particularly in astrocytes, including GFAP , BDNF , SOD2 , SLC1A3 , MAOA , ACHE , APOE , LDLR , which encode astrocyte markers and proteins associated with trophic signaling, antioxidant defenses, neurotransmitter homeostasis and cholesterol metabolism.…”
Section: Zikv Infection and Potential Neurological Complications Rela...mentioning
confidence: 99%
“…West Nile virus is also known to cause a neuroinvasive disease manifesting meningitis, meningoencephalitis, encephalitis, or acute flaccid paralysis, commonly associated with diarrhea/vomiting, weakness, impaired vision, confusion, or drowsiness, and shows elevated levels of proinflammatory cytokines IL4, IL6, and IL10 in serum samples (138). Finally, Zika virus can infect the CNS and induce microcephaly in fetuses and rare but serious neurological diseases in adults, which are associated with excessive production of IFNa, IFN-b, IL-6, and TNF-a (139).…”
Section: Neurological Affectation Upregulated Cytokines Referencesmentioning
confidence: 99%
“…Interestingly, ZIKV targets various cells in the brain, including radial glial cells, neural progenitor cells (NPCs), astrocytes, microglial and glioblastoma stem cells, affecting these brain cells by different mechanisms, such as apoptosis and cell cycle dysregulation, which may induce neurological complications and neuroimmunopathogenesis (Komarasamy et al, 2022), possibly causing the depletion of neural progenitors in the cortical layer of the brain (Ihunwo et al, 2022). Indeed, cell‐intrinsic innate immune responses to ZIKV infection profoundly shape neuronal transcriptional profiles by inducing changes to neurologic gene expression associated with psychiatric disorders (Kung et al, 2022). Noteworthy, we have previously observed a correlation between a lower Ndel1 activity and inflammatory marker interleukin‐4 (IL‐4) levels in patients with chronic schizophrenia (Nani et al, 2022).…”
Section: Discussionmentioning
confidence: 99%